Mobile Heatlh Berbasis Smartphone untuk Kemampuan Ibu Menyusui secara Eksklusif - Dewi, Mariza Mustika; Ahmaniyah, Ahmaniyah; Rochkmana, Meika Jaya (Fakultas Ilmu Kesehatan, 2024)
Educational media in the implementation of exclusive breastfeeding plays a very big role in increasing mothers' knowledge and attitudes in order to give birth to breastfeeding actions and skills. Mobile health or mobile-based health or mhealth is one of WHO's recommendations, namely a form of care in the field of education which is expected to be able to overcome health problems by reducing costs, energy and care time. The aim of this research is to determine the effectiveness of smartphone-based mobile health in improving the ability of breastfeeding mothers. exclusively Method: This research is a literature review. Article searches were carried out using several databases with publications in 2014-2024 with the keywords mobile application for exclusive breastfeeding